Penerapan Logika Fuzzy untuk Menentukan Jumlah Produksi Beras Berdasarkan Data Persediaan dan Jumlah Permintaan (Studi Kasus UD Siregar Wonomulyo) - Indra (STMIK KHARISMA Makassar, 2016)
The maximum benefit is obtained from the maximum sales. If the number of products manufactured by the company is less than the demand, the company will lose the opportunity to gain the maximum profit and vice versa. Therefore, planning the number of products in the UD. SIREGAR very important. In order to meet market demand with the right and by a corresponding amount. Factors to consider in determining the amount of the product, among other things: the amount of supply and demand. Writing and discussion in this study is about Fuzzy, Use case, class diagrams, object diagrams, activity diagrams, application of Fuzzy to determine the amount of production is based on the number of request and supplies, and the draft form Application of Fuzzy Logic for Determining the Total Production of Goods Data Inventory and number of requests at UD. SIREGAR To create a draft program that is expected to be applied and used, so as to help the process of determining the amount of production and inventory and request based on UD. SIREGAR Fuzzy Logic in determining the amount of rice based on the number of supply and demand that has been built can be used to assist companies in taking a decision with the truth value reaching 98.41902%.